Essential Oil from Lemongrass Extracted by Supercritical Carbon Dioxide and Steam Distillation - Ha, Huynh K. P.; Maridable, Julius; Gaspillo, P.; Hasika, M.; Malaluan, R.; Kawasaki, J. (2008)
This study compares the composition of essential oil extracted from lemongrass leaves and stems using supercritical CO2 (SC CO2) and steam distillation. In the process using SC CO2 extraction in a Supercritical Fluid Extraction System (SFE), the temperature of extraction was varied from 35–50 0C, while the pressure applied was 9.1–11.1 MPa. The flow rate of CO2 to the reactor was maintained at 0.5 m3 h-1. Steam distillation was conducted using a standard bench scale setup. The extracts from both methods were analyzed by gas chromatography - mass spectrometry (GC-MS) and the variations of the composition were reported. The study showed that better oil quality in terms of composition was produced from the air dried raw materials than from direct heat drying. The essential oil extracted from air dried lemongrass leaves by SFE process contained 94.4% citral, 1.14% myrcene and 0.5% limonene, showing a composition similar to the reference standard. In contrast, the oil from the air dried lemongrass stems fell short in terms of purity. SFE was found to be a superior process than steam distillation, producing better quality essential oil containing 90% Citral.
Keywords: Essential oils; Lemon grass